O uso da história da ciência no ensino de física : o que pensam os professores? - Mazia, Carlos Noel (2014)
Current investigation analyzes the perception that a group of teachers has on the use of History of Science in the teaching of Physics in basic education. A diagnostic description is provided of the school's response to the challenges posed in its relationship with society and ambiguous manner it faces them. Discussions ensues on the need that teachers have to acquire adequate concepts of nature of Science for an efficient work in scientific literacy, with special emphasis on the use of the History of Science in this task. Versions of the History of the History of Science that foreground ambiguous views on scientific work and on the respective caution in didactic transposition are analyzed. Further, U. S. projects on the teaching of Physics are discussed, 'contrary' to the adoption of the History of Science, and on the contents of the History of Science in education were analyzed, following the methodological framework of Husserl's phenomenology. The convergence of these discourses did not suggest any resistance with regard to the use of the History of Science, except a lack of perspectives that could be viewed through the open windows of their daily experience in school.